Column tests for evaluation of the enzymatic biodegradation capacity of hydrocarbons (C10–C50) contaminated soil. (1st December 2021) - Kadri, Tayssir; Robert, Thomas; Rouissi, Tarek; Sebastian, Joseph; Magdouli, Sara; Brar, Satinder Kaur; Martel, Richard; Lauzon, Jean-Marc
Abstract: Though many studies pertaining to soil bioremediation have been performed to study the microbial kinetics in shake flasks, the process efficiency in column tests is seldom. In the present study, soil columns tests were carried out to study the biodegradation of soil contaminated with a high concentration of diesel (≈19.5 g/kg) petroleum hydrocarbons expressed as C10 –C50 . Experiments were done with crude enzymatic cocktail produced by the hydrocarbonoclastic bacterium, Alcanivorax borkumensis. A. borkumensis was grown on a media with 3% (v/v) motor oil as the sole carbon and energy source. The effects of the enzyme concentration, treatment time and oxidant on the bioremediation efficiency of C10 –C50 were investigated. A batch test was also carried out in parallel to investigate the stability of the enzymes and the effect of the biosurfactants on the desorption and the bioconversion of C10 –C50 . Batch tests indicated that the biosurfactants significantly affected the desorption and alkane hydroxylase and lipase enzymes, maintained their catalytic activity during the 20-day test, with a half-life of 7.44 days and 8.84 days, respectively. The crude enzyme cocktail, with 40 U/mL of lipase and 10 U/mL of alkane hydroxylase, showed the highest conversion of 57.36% after 12 weeks of treatment with a degradation rate of 0.0218 day −1 . The results show that the soil column tests can be used to optimize operating conditions for hydrocarbon degradation and to assess the performance of the overall bioremediation process. Graphical abstract: Image 1 Highlights: Soil column test to assess enzymatic hydrocarbon degradation. Crude enzyme from Alcanivorax borkumensis used for bioremediation. Optimal enzyme concentrations of 40 U/ml (lipase) and 10 U/ml (alkane hydroxylase). About 48.35% degradation after 6 weeks of enzymatic pretreatment. About 57.36% degradation after 12 weeks and degradation rate of 0.0218 day −1 .